The association between sedentary behavior, exercise, and sleep disturbance: A mediation analysis of inflammatory biomarkers - You, Yanwei; Chen, Yuquan; Fang, Wen; Li, Xingtian; Wang, Rui; Liu, Jianxiu; Ma, Xindong (Frontiers in Immunology, 2023)
Background: Two related lifestyle behaviors associated with sleep disturbance are sedentary behavior and physical exercise participation. We aimed to use a population-based study to disentangle the relationships between sedentary behavior, exercise, and sleep disturbance based on the blood-cell based inflammatory biomarkers. Methods: A total of 22,599 participants from the National Health and Nutrition Examination Survey (NHANES) were included in the analyses. Sleep disturbance was assessed according to the NHANES questionnaire. Exercise participation and sedentary behavior were evaluated by the global physical activity questionnaire. The inflammatory biomarkers in the examination were white blood-cell (WBC) count, neutrophil count (NEU), neutrophil-to-lymphocyte ratio (NLR) and systemic immune-inflammation index (SII). Complex multi-stage sampling design and weighted multivariable logistic regression were applied for further analysis. Mediation models were constructed to figure out the mediating role of inflammatory biomarkers. Results: The weighted prevalence of sleep disturbance was 24.17%. Sedentary behavior and exercise were associated with sleep disturbance after fully adjustment [For sedentary behavior, OR (95% CI): 1.261(1.154,1.377); for exercise, OR (95% CI): 0.849 (0.757,0.953)]. In severe sedentary behavior groups, the mitigation effect of exercise on sleep disturbance was observed with [ORs] (95% CIs) 0.687 (0.551,0.857). For the mechanism, the strongly associations were detected between inflammatory biomarkers and sleep disturbance. Mediation analysis showed that WBC, NEU, NLR, and SII mediating the statistical association between sedentary behavior and sleep disturbance with proportion mediated (%) as 2.09, 2.27, 1.76, 0.82, respectively. Conclusions: Our data suggested that sedentary behavior was a risk factor for sleep disturbance. Blood-cell based inflammatory biomarkers was not only an easily accessible and cost-effective strategy for identifying sleep disturbance, but also significantly mediated the association between sedentary behavior and sleep disturbance. Exercise was proved to be effective in severe sedentary behavior groups to improve sleep disturbance symptoms, while the internal mechanism needed further exploration.